The crash course : the unsustainable future of our economy, energy and environment - Martenson, Chris, ....- (Hoboken : Wiley, 2011)
The next twenty years will be completely unlike the last twenty years. The world is in economic crisis, and there are no easy fixes to our predicament. Unsustainable trends in the economy, energy, and the environment have finally caught up with us and are converging on a very narrow window of time the Twenty-Teens. The Crash Course presents our predicament and illuminates the path ahead, so you can face the coming disruptions and thrive--without fearing the future or retreating into denial. In this book you will find solid facts and grounded reasoning presented in a calm, positive, non-partisan manner. Our money system places impossible demands upon a finite world. Exponentially rising levels of debt, based on assumptions of future economic growth to fund repayment, will shudder to a halt and then reverse. Unfortunately, our financial system does not operate in reverse. The consequences of massive deleveraging will be severe. Oil is essential for economic growth. The reality of dwindling oil supplies is now internationally recognized, yet virtually no developed nations have a Plan B. The economic risks to individuals, companies, and countries are varied and enormous. Best-case, living standards will drop steadily worldwide. Worst-case, systemic financial crises will toss the world into jarring chaos. This book is written for those who are motivated to learn about the root causes of our predicaments, protect themselves and their families, mitigate risks as much as possible, and control what effects they can. With challenge comes opportunity, and The Crash Course offers a positive vision for how to reshape our lives to be more balanced, resilient, and sustainable.
Includes bibliographical references and index.
Keywords: United States -- Economic conditions -- 2009-.; Sustainable development -- United States; Economic forecasting -- United States